FOR A REFORMULATION OF A LOCAL SOCIAL INTERVENTION - Morais, Carminda; Gomes, Daniela; Valerio, Miguel Angelo (European Scientific Journal, ESJ, 2013)
This article presents the theoretical and practical framework of the project “Capacitate to Qualification and Innovation in Social Networks of Minho-Lima” (CQIRS in Portuguese) within the Social Network Programme, in the local context of ten municipalities. It is addressed the theoretical approaches of local development and of the programme that have been in the basis of CQIRS planning and framing. Therefore, the main purposes and actions of the project are exposed, as well as the development, operationalization and evaluation of some actions concluded, but also the stadium of the remaining actions.